The library innovation toolkit : ideas, strategies, and programs - Molaro, Anthony; White, Leah L. (ALA Editions, an imprint of the American Library Association, 2015)
Progress for the sake of progress is all too often a drain on precious time and resources. The communities and users that libraries serve are always changing; true innovation helps libraries adapt to meet their needs and aspirations both now and in the future. This collection offers snapshots of innovation in action at a range of libraries, showcasing ideas and initiatives that will inspire librarians at their own institutions. Among the topics covered are: the importance of creating organizational structures that lead to innovation; strategies for getting library staff and other stakeholders on board and engaged, complete with a step-by-step toolkit for achieving innovative outcomes; ways to expand the library beyond its walls to deliver exceptional and innovative services to library users; money-saving initiatives that use technology to improve users' experience; and innovative uses of library spaces, such as designing and implementing a digital media lab.